Reading thousands of books and traveling thousands of miles: Diversity of life experience mediates the relationship between family SES and creativity. Issue 2 (8th November 2019) - Xu, Xiaobo; Pang, Weiguo
Abstract : This study examined the relationship between family SES and children's creativity, and tested the mediating role of diversity of life experience in this relationship. A total of 204 undergraduates (54 males and 150 females), aged between 17 and 23 years, completed a family SES questionnaire, diversity of life experience questionnaire, biographical inventory of creative behaviors, and alternative uses tasks (AUT). The results showed positive associations between family SES, diversity of life experience, and different indices of creativity. Additionally, mediation analyses indicated that diversity of life experience fully mediated the effect of family SES on creative behavior and AUT originality. In accordance with the family investment model, these results confirmed the positive association between family SES and creativity, and identified diversity of life experience as a mediating variable through which family SES influences creativity performance. Implications and future directions are discussed in detail.